Reassessing Journalism and Media Dynamics for Sustainable Development of Nigeria: Views of Asaba Residents - Guanah, Jammy Seigha; Okowa-Nwaebi, Loveth; Ezekwelu, Kingsley Chukwudubem; Ridwan, Muhammad (Budapest International Research and Critics University, 2024)
In the global development agenda context, particularly the United Nations’ Sustainable Development Goals (SDGs), the media are positioned as key actors capable of shaping public discourse, influencing policy, and raising awareness on critical issues. Hence, to examine the role of journalism and media in promoting sustainable development in Nigeria, this paper aimed to assess whether journalism and media have effectively contributed to sustainable development across Nigeria; investigate the extent to which media in Nigeria have supported national sustainable development initiatives, and identify the challenges they face in this endeavour. The study was guided by the Media Development Theory, which emphasises the role of the press in advancing national development priorities. The findings were that journalism and media have partially contributed to sustainable development across Nigeria, and, that, the media in Nigeria, to some extent, have not been adequately supporting national sustainable development initiatives in Nigeria. The study also revealed that the media face different types of challenges in the cause of performing their duties as agents of sustainable development, particularly in developing nations like Nigeria. The study recommended that there should be an enabling environment that allows the media to function effectively as catalysts for sustainable development. Besides, the study recommended that there should be a collaborative effort between media organisations, governments, and civil society so as to overcome the structural and institutional barriers that limit media's contribution to development. Lastly, journalism and media must be empowered to operate freely, independently, and with the resources necessary to engage with complex development issues so as to fulfill their role in promoting sustainable development, particularly in Nigeria.